Using Podcasts to Change Learners’ Attitudes and Beliefs in Learning / Teaching English as a Second Language: A Case Study in Secondary Education in Greece - Nikolou, Stamatina; Darra, Maria (International Journal of Educational Studies, 2019)
The main objective of this study is to explore how podcasting can be implemented in teaching English as a Second Language as a supportive technological tool and thus contribute to the development of positive attitudes and beliefs of the learners. To this aim, the field experiment research was conducted. The study was carried out with a total of 28 pupils of the first grade of high school at an educational institution on Rhodes, Greece in February 2018. The students were assigned to the experimental group (15 students) and the control group (13 students). The results of the research have shown a positive change in students? attitudes and beliefs, though no statistically significant difference has arisen regarding the students? interest in the course, their self-confidence in English, the role of gender in learning English, and the difficulties students come across when studying English. Similarly, no significant change has occurred regarding the usefulness of English, the importance of the English accent, and the knowledge of another foreign language as a contributing factor to learning English more easily. Finally, a negative change was found regarding difficulties in oral communication in English.